Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Kota Surakarta Tahun 1993 - 2013 - YURISWADI, Titi Darpita Danti; , Dr. Daryono Soebagyo, M.Ec (2014)
This study entitled "Factors Affecting Economic Growth in Surakarta from 1993 to 2013". This study aimed to analyze the influence of population, labor, local government spending, and inflation on economic growth of Surakarta. The method of analysis used in this study is the regression of Partial. Adjustment Model (PAM). Furthermore, this study were tested using the classical assumption and statistical tests. The classical assumptions used in this study are multicolinearity test, residual normality test, heteroscedasticity test, autocorrelation test, and test specification models. While the statistical tests used in the study are the F test statistic, t test statistic, and the coefficient of determination (R2). The results showed that the variables of population and employment in the short-term and long-term had negative effect and unsignificant on economic growth of the city of Surakarta, local government spending variable had positive effect and unsignificant on economic growth of the city of Surakarta, while the inflation variables had negative effect and significant on the economic growth of the city of Surakarta.